Ancient sundials from Moesia and Thracia (The sundial found at Montand) - Valev, Peter (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes ancient sundials from the regions of Moesia and Thrace, with particular emphasis on the find from Montana. The problem is significant for studies on the development of technology and science in the ancient world. The aim of the work is to determine the typology, function, and methods of construction of sundials. The author applies archaeological analysis and mathematical-geometrical methods. The most important results indicate that several types of sundials (including spherical, cylindrical, and planar) have been discovered in present-day Bulgaria, and the example from Montana belongs to the rare group of cylindrical sundials. The analysis also shows that these devices were used both for measuring time and organizing daily life (e.g., guard shifts). The article also discusses methods of reconstructing parameters such as the length of the gnomon or geographical latitude. The conclusion emphasizes the high level of astronomical and engineering knowledge in antiquity.